HCV infection activates the proteasome via PA28γ acetylation and heptamerization to facilitate the degradation of RNF2, a catalytic component of polycomb repressive complex 1 - Hirotake Kasai; Atsuya Yamashita; Yasunori Akaike; Tomohisa Tanaka; Yoshiharu Matsuura; Kohji Moriishi (mBio)
ABSTRACT We previously reported that hepatitis C virus (HCV) infection or HCV core protein expression induces HOX gene expression by impairing histone H2A monoubiquitination via a proteasome-dependent reduction in the level of RNF2, a key catalytic component of polycomb repressive complex 1 (H. Kasai, K. Mochizuki, T. Tanaka, A. Yamashita, et al., J Virol 95:e01784-20, 2021, https://doi.org/10.1128/jvi.01784-20). In this study, we aimed to investigate the mechanism by which HCV infection accelerates RNF2 degradation. Yeast two-hybrid screening and an immunoprecipitation assay revealed that RNF2 is a PA28γ-binding protein. The proteasome activator PA28γ destabilized the RNF2 protein in a proteasome-dependent manner, since RNF2 degradation was impaired by PA28γ knockout or MG132 treatment. HCV infection or core protein expression reduced the levels of RNF2 and histone H2A K119 monoubiquitination and induced the expression of HOX genes in the presence of PA28γ, while PA28γ knockout reversed these changes. Treatment with a lysine acetyltransferase inhibitor inhibited the acetylation of PA28γ at K195 and the degradation of the RNF2 protein, while treatment with a lysine deacetylase inhibitor accelerated these events in a PA28γ-dependent manner. RNF2 protein degradation was increased by expression of the acetylation mimetic PA28γ mutant but not by expression of the acetylation-defective mutant or the proteasome activation-defective mutant. Furthermore, HCV infection or core protein expression facilitated the interaction between PA28γ and the lysine acetyltransferase CBP/p300 and then accelerated PA28γ acetylation and heptazmerization to promote RNF2 degradation. These data suggest that HCV infection accelerates the acetylation-dependent heptamerization of PA28γ to increase the proteasomal targeting of RNF2.IMPORTANCEHCV is a causative agent of HCV-related liver diseases, including hepatic steatosis, cirrhosis, and hepatocellular carcinoma. PA28γ, which, in heptameric form, activates the 20S core proteasome for the degradation of PA28γ-binding proteins, is responsible for HCV-related liver diseases. HCV core protein expression or HCV infection accelerates RNF2 degradation, leading to the induction of HOX gene expression via a decrease in the level of H2Aub on HOX gene promoters. However, the mechanism of RNF2 degradation in HCV-infected cells has not been clarified. The data presented in this study suggest that PA28γ acetylation and heptamerization are promoted by HCV infection or by core protein expression to activate the proteasome for the degradation of RNF2 and are responsible for HCV propagation. This study provides novel insights valuable for the development of therapies targeting both HCV propagation and HCV-related diseases.